ANALYSIS OF POWER SYSTEMS EFFICIENCY BY GRAPH BUILT - Draganov, B. (Energy and Automation, 2016)
Given the basics of graph-theoretic constructions. Set the method of assessing the energy efficiency of regenerative heat exchanger based on graph topological constructions.